2019
DOI: 10.1371/journal.pone.0209461
|View full text |Cite
|
Sign up to set email alerts
|

Seeing emotions, reading emotions: Behavioral and ERPs evidence of the regulation of pictures and words

Abstract: Background Whilst there has been extensive study of the mechanisms underlying the regulation for pictures, the ability and the mechanisms beyond the regulation of words remains to be clarified. Similarly, the effect of strategy when applying a regulatory process is still poorly explored. The present study seeks to elucidate these issues comparing the effect of regulation and of strategy to both neutral and emotional words and pictures. Methodology/Principal findings Thi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 71 publications
(116 reference statements)
3
32
1
Order By: Relevance
“…The LPP is a late ERP that is linked to neuromodulatory processes [64] and is larger in response to arousing pictures (e.g., [63,65]). Our results are in line with results from Krendl et al [39], or Grecucci [40], but contrary to the majority of earlier studies which showed a decreased LPP for reappraisal [36,37,66]. A possible reason for these heterogeneous findings may be differing cognitive demands in reappraising emotional information, which may be reflected in LPP amplitude differences.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The LPP is a late ERP that is linked to neuromodulatory processes [64] and is larger in response to arousing pictures (e.g., [63,65]). Our results are in line with results from Krendl et al [39], or Grecucci [40], but contrary to the majority of earlier studies which showed a decreased LPP for reappraisal [36,37,66]. A possible reason for these heterogeneous findings may be differing cognitive demands in reappraising emotional information, which may be reflected in LPP amplitude differences.…”
Section: Discussionsupporting
confidence: 90%
“…Greater LPP amplitudes were associated with more intense/arousing stimuli [34] and decreased LPP amplitudes might reflect neuromodulatory activity, e.g., downstreaming processes in response to increased activation of the amygdala (e.g., [7]). Studies showed decreased LPP amplitudes after suppression (e.g., [35]) and after reappraisal of negative emotional stimuli (e.g., [36,37,38] but see [39,40]).…”
Section: Introductionmentioning
confidence: 99%
“…Besides magnetic resonance imaging results, emotion-regulation-related processes are also reflected in changes in electrocortical potentials (event-related potentials). A recent experiment showed an increase in a negative fronto-central component named stimulus-preceding negativity (SPN), when individuals implemented a regulation strategy [ 45 ]. When participants applied the regulation strategy to emotional stimuli, a decrease in the late positive potential (LPP) elicited by emotional stimuli was repeatedly found [ 45 , 46 , 47 ].…”
Section: Anxiety Regulation and Its Neural Bases: The Cognitive VImentioning
confidence: 99%
“…A recent experiment showed an increase in a negative fronto-central component named stimulus-preceding negativity (SPN), when individuals implemented a regulation strategy [ 45 ]. When participants applied the regulation strategy to emotional stimuli, a decrease in the late positive potential (LPP) elicited by emotional stimuli was repeatedly found [ 45 , 46 , 47 ]. Last but not least, the regulation strategy also affects brain oscillatory activity, with a modulation of theta frequencies [ 48 ], interpreted as a cortico-subcortical interaction between modulating and modulated brain regions, but also as a sign of increased relaxation after having regulated emotions.…”
Section: Anxiety Regulation and Its Neural Bases: The Cognitive VImentioning
confidence: 99%
“…Although emotion regulation was initially intended as a field of basic research, clinicians quickly understood its relevance for their practice. Studying the mechanisms involved in the regulation of emotions is particularly relevant when considering the failure to regulate interpersonal emotions and emotionally driven behaviors that characterize psychiatric disorders (Kring and Werner, 2004;Ochsner and Gross, 2008;Grecucci, 2012;Giorgetta et al, 2012Giorgetta et al, , 2014Grecucci et al, 2015bGrecucci et al, , 2019Messina et al, 2016;De Panfilis et al, 2019;Sorella et al, 2019). Nearly all psychiatric disorders include one or more primary dysregulated emotions (e.g., anger in borderline personality disorder, sadness in depression, fear in anxiety disorders, shame in narcissistic personality disorders, etc.…”
Section: Introductionmentioning
confidence: 99%